Cytogenetic Alterations and Correlation with Age and Gender in Patients of Multiple Myeloma: A Study from a Tertiary Care Center in Eastern India - Jha, Karuna; Saha, Sandeep; Bhattacharyya, Maitreyee (South Asian Journal of Cancer, 2024)
Background Multiple myeloma is a cytogenetically heterogeneous, evolving, and incurable disease. Differences in prevalence of myeloma already exist in Indian subcontinent as compared with Western world countries. This study attempts to investigate differences in incidence of cytogenetic abnormalities (CA) in Eastern Indian patients and study differences in incidence with respect to age and gender.Materials and Methods Interphase fluorescence in situ hybridization (FISH) was applied on purified plasma cells of 280 newly diagnosed myeloma cases using specific probes.Statistical Analysis Data was analyzed using SPSS software version 25.Results Note that 51.07% patients were FISH positive. Del13q was the most common CA. Significant association of del 13q with t(4;14), del 17p, and gain of 1q was seen. The frequencies of FISH positive and negative groups differed in the different age groups; higher number of cases in 41 to 50 years group in FISH positive group (p < 0.05) and lower number of cases in FISH positive group in 61 to 70 years (p < 0.05) as compared with FISH negative group. Del 17p had higher number of cases in age group 41 to 50 years and 51 to 60 years as compared with other age groups. Incidence of t(11;14) was in 5th to 7th decade while del 13q and t(4;14) had the widest range of age at presentation. Gender disparities were seen in high-risk cytogenetics like del 17p and 1q gain.Conclusion The differences in incidence rate of CAs per se in myeloma cases diagnosed in Indian subcontinent and the differences in incidence with respect to age and gender warrant further multicentric studies.
Keywords: myeloma; FISH; cytogenetic aberrations; age; gender